Comunicação de marcas de moda: nova proposta para a ação do Relações Públicas - Camargo, Marina Franco [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This study has the objective of presenting a new suggestion to the public relations professional into the Brazilian fashion business, seeing that, besides promising and little explored, presents social-economic conditions that allow the profession actuation. For this, it has been deeply analyzed the social character of fashion history e its development parallel to the society historical and economic transformations, basing, then, the study of fashion history in Brazil. To understand contemporaneity and the relations which interlace on it, there were used two analyzes about nowadays social order, liquid pos-modernity, from Bauman; and the hypermodernity, from Lipovetsky. In this context, it‟s approached new ways of relating with marks and with products which, since their consumption, are prepared to posterior discard. In the accelerated scenario of marks and consumption, the human relations, more liquids and tenuous, create the urgent possibility of action from on communication professional, who knows to identify the consumers desires and foresee their needs, rendering the tenuous laces stronger and the relationships more solid. This is when the profession of public relations presents itself as a new proposal to create experiences and to tight the loose laces on the consumption era

Este trabalho tem como objetivo apresentar uma nova proposta de exercício do profissional de relações públicas junto ao mercado de moda brasileiro, visto que, além de promissor e pouco inexplorado, apresenta condições sócio-econômicas propícias para a atuação do profissional. Para tanto, foi analisada a fundo o caráter social da história da moda e seu desenvolvimento paralelo às transformações histórico-econômicas da sociedade, embasando, então, o estudo da história da moda no Brasil. Para compreender a contemporaneidade e as relações que nela se entrelaçam, foram abordadas duas análises a respeito da ordem social atual, a de pós-modernidade líquida, de Bauman; e a de hipermodernidade, de Lipovetsky. Nesse contexto, abordam-se as novas maneiras de se relacionar com as marcas e com os produtos que, desde o seu consumo, são preparados para o posterior descarte. No cenário acelerado de marcas e consumo, as relações humanas, mais líquidas e tênues, criam a possibilidade urgente da ação de um profissional de comunicação que saiba identificar os desejos dos consumidores e antever suas necessidades, tornando os laços tênues mais fortes e os relacionamentos mais densos. É então que a profissão de relações públicas se apresenta como uma nova proposta para criar experiências e amarrar os laços soltos da era do consumo
Keywords: Moda; Civilização moderna; Relações publicas; Marca de produtos